2023
DOI: 10.3102/0013189x231206172
|View full text |Cite
|
Sign up to set email alerts
|

Language Views for Scientific Sensemaking Matter: A Synthesis of Research on Multilingual Students’ Experiences with Science Practices Through a Translanguaging Lens

María González-Howard,
Sage Andersen,
Karina Méndez Pérez
et al.

Abstract: This synthesis examines recent science education research on multilingual students’ experiences with language-rich science practices. Adopting a translanguaging lens, we explore how researchers’ language conceptualizations impact the science practices they study and the ways multilingual students are positioned. This analysis helps us understand the extent to which recent research is disrupting, or sustaining, minoritizing narratives about multilingual students and how they sensemake in science. Based on our f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Findings from an analysis of course artifacts and interviews indicated that preservice teachers expressed relatively narrow understandings of language, science, and their integration (González‐Howard et al, 2022). For example, they conceived of language in terms of named languages with rigidly constructed boundaries (e.g., “Spanish” vs. “English”), in contrast with the fluid conceptualization of translanguaging (García & Li, 2014).…”
Section: Emerging Research In Science Education With Mlsmentioning
confidence: 99%
See 4 more Smart Citations
“…Findings from an analysis of course artifacts and interviews indicated that preservice teachers expressed relatively narrow understandings of language, science, and their integration (González‐Howard et al, 2022). For example, they conceived of language in terms of named languages with rigidly constructed boundaries (e.g., “Spanish” vs. “English”), in contrast with the fluid conceptualization of translanguaging (García & Li, 2014).…”
Section: Emerging Research In Science Education With Mlsmentioning
confidence: 99%
“…This is consistent with a finding of the National Academies of Sciences Engineering and Medicine (2022) report that their fourth approach to equity—“seeing science and engineering as part of justice movements” (p. 25)—was significantly underrepresented in the literature. Moreover, research on preservice teacher preparation has pointed to the difficulty faced by teachers, many of whom do not share the cultural backgrounds of their students, in “identifying and integrating [MLs'] funds of knowledge into their instruction” (Rutt et al, 2021, p. 656), although this difficulty is not exclusive to English‐monolingual teachers (e.g., González‐Howard et al, 2022). Future research should leverage this unprecedented moment in which societal challenges loom large (e.g., COVID‐19, climate change) to support teachers in eliciting and cultivating MLs' rich knowledge and experiences related to these challenges (Calabrese Barton, Greenberg, Turner et al, 2021; Lee & Campbell, 2020; Lee & Grapin, 2022).…”
Section: Research Agenda For Science Education With Mlsmentioning
confidence: 99%
See 3 more Smart Citations